Liposomes as novel anti-infectives targeting bacterial virulence factors?. Issue 5 (May 2015) - Azeredo da Silveira, Samareh; Perez, Antonio
<x xml:space="preserve">Abstract</x> A recent report commissioned by Prime Minister David Cameron and chaired by former Goldman Sachs chief economist Jim O'Neill warns that the emergence, persistence and spread of antimicrobial resistance could lead to 10 million deaths per year and cause an economic burden as much as US$100 trillion by 2050. In the midst of this global crisis, unprecedented paths are being explored to combat bacterial infection. Virulence factors, and more particularly pore-forming toxins, play a key role in increasing morbidity and mortality caused by drug-resistant bacterial infections. Novel anti-infective liposomes specifically targeting and neutralizing these cytotoxic toxins are potential game-changers in the fight against deadly infections.